2014
DOI: 10.5152/etd.2014.8416
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hand Functions in Patients with Chronic Hepatitis B

Abstract: Objective: Motor dysfunction is an important clinical finding in patients with liver cirrhosis (LC), but there is no study assessing fine motor coordination in patients with chronic hepatitis B (CHB). We aimed to investigate hand functions and fingertip dexterity in patients with CHB. Materials and Methods: A total of 17 female and 15 male patients diagnosed with CHB without histopathological findings of cirrhosis were enrolled to the study; 21 female and 9 male healthy volunteers were included as a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…HGS evaluates the nutritional status and the menace of falling [ 24 , 28 ]; is associated with the muscle mass [ 23 , 25 ]; is an indicator of walking speed and sarcopenia [ 23 , 26 ]; and is associated with the quality of life [ 27 ]. Even though HGS was largely evaluated in patients with chronic liver diseases, to the best of the authors’ knowledge, only two previous studies explored the HGS in non-cirrhotic CHB (NC-CHB) patients compared to healthy participants [ 28 , 29 ]. The first study reported that the healthy participants ( n = 30) and the patients with CHB ( n = 32) had comparable values of HGS in both dominant and non-dominant hands [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…HGS evaluates the nutritional status and the menace of falling [ 24 , 28 ]; is associated with the muscle mass [ 23 , 25 ]; is an indicator of walking speed and sarcopenia [ 23 , 26 ]; and is associated with the quality of life [ 27 ]. Even though HGS was largely evaluated in patients with chronic liver diseases, to the best of the authors’ knowledge, only two previous studies explored the HGS in non-cirrhotic CHB (NC-CHB) patients compared to healthy participants [ 28 , 29 ]. The first study reported that the healthy participants ( n = 30) and the patients with CHB ( n = 32) had comparable values of HGS in both dominant and non-dominant hands [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though HGS was largely evaluated in patients with chronic liver diseases, to the best of the authors’ knowledge, only two previous studies explored the HGS in non-cirrhotic CHB (NC-CHB) patients compared to healthy participants [ 28 , 29 ]. The first study reported that the healthy participants ( n = 30) and the patients with CHB ( n = 32) had comparable values of HGS in both dominant and non-dominant hands [ 29 ]. The second study noted that healthy participants ( n = 159) and patients with chronic hepatitis ( n = 189) including some patients with CHB ( n = 80) had comparable values of HGS in the non-dominant hand [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations